Biological profile of tartrate-resistant acid phosphatase as a marker of bone resorption (Revista Española de Fisiología, 1990)
Tartrate-resistant serum acid phosphatase was measured in 123 subjects, 80 of which were normal and the rest pathologic, in order to define the profile and value of this parameter as a biological marker of osteoclastic activity. Normal subjects were divided into age groups based on the period where skeletal growth ends (under 20 years), at the age of menopause in women (50 years, between 20 and 50 years) and those over 50 years. There was an increase in tartrate-resistant serum acid phosphatase coinciding with puberty and no sex differences were observed after the 50 year mark, when women showed higher values than men (p less than 0.001). Such tartrate-resistant serum acid phosphatase increase, is reflected as higher values in the 50 year group than in the 20 to 50 year group (p less than 0.001), the only age limit where a negative significant correlation between tartrate-resistant serum acid phosphatase values and age could be observed (p less than 0.05). Values were higher up to the age of 20 years (p less than 0.001) than in any other older age group. Levels increased significantly (p less than 0.001 for both groups) in post-menopausal osteoporosis (n = 20) and in Paget's disease of bone (n = 15), and decreased significantly (p less than 0.05) in imperfect osteogenesis (n = 8), thus revealing its value as a biological marker of osteoclastic activity.